2011
DOI: 10.1002/chem.201100472
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Power Adjustment of Surface‐Regulating Polymers for Shaping Gold Polyhedral Nanocrystals

Abstract: PVP (poly(vinyl pyrrolidone)) is a common polymer that behaves as a surface-regulating agent that shapes metal nanocrystals in the polyol process. We have used different polymers containing tertiary amide groups, namely PVCL (poly(vinyl caprolactam)) and PDMAm (poly(N,N-dimethyl acrylamide)), for the synthesis of gold polyhedrons, including octahedrons, cuboctahedrons, cubes, and higher polygons, under the present polyol reaction conditions. The basicity and surface coordination power of the polymers are in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
(38 reference statements)
2
19
0
Order By: Relevance
“…Signal-shiing of 1.0, 0.3 and 0.9 eV was observed for N1s and O1s (C-O) and O1s (C]O) signals, respectively. Similar XPS signal-shiing phenomena were also reported on poly(vinyl pyrrolidone) (PVP) or PNVCL-coated gold nanocrystals, 43 PVPcoated silver nanowires, 44 and PVP-coated platinum nanoparticles, 45 due to the interaction between metallic atoms and nitrogen and/or oxygen atoms. Therefore, these data support that the PVOH-b-PNVCL macromolecular chains immobilize onto the surface of the gold cores through the interaction between gold atoms and O or N atoms, as already reported.…”
Section: Resultssupporting
confidence: 71%
“…Signal-shiing of 1.0, 0.3 and 0.9 eV was observed for N1s and O1s (C-O) and O1s (C]O) signals, respectively. Similar XPS signal-shiing phenomena were also reported on poly(vinyl pyrrolidone) (PVP) or PNVCL-coated gold nanocrystals, 43 PVPcoated silver nanowires, 44 and PVP-coated platinum nanoparticles, 45 due to the interaction between metallic atoms and nitrogen and/or oxygen atoms. Therefore, these data support that the PVOH-b-PNVCL macromolecular chains immobilize onto the surface of the gold cores through the interaction between gold atoms and O or N atoms, as already reported.…”
Section: Resultssupporting
confidence: 71%
“…Various kinds of morphology investigated includes nanowires, nanorods, nanoprisms, nanoplates, polyhedral structures, etc. [43][44][45][46] Furthermore, the synthesis of nanoparticles with exposed high-energy or active facets has attracted considerable attention as well, because they usually exhibit fascinating interfacial behavior and have been applied in technological applications. 47,48 Most of the conventional methods of loading of metal nanoparticles over GO surface includes the use of some reducing agents such as surfactants and polymers, which have the limitation of impurity in crystal lattice of the final nanocomposite.…”
Section: Metal Nanoparticles-graphene Oxide Nanocompositesmentioning
confidence: 99%
“…The pyrrolidone side chain in PVP preferentially interacts with metal ions and specific facets of the nanoparticles, which increments particle size and causes anisotropic growth. 16 Yanai et al recently reported that the MOF crystal size is increased in the presence of PVP, and observed that PVP acts as a weak capping ligand for decreasing the number of nucleation points. 17 The increase in MOF crystal size with PVP, observed in this work, agrees with these past findings.…”
Section: −1mentioning
confidence: 99%